A model of knowledge management readiness and its contributing factors - Mohamed Jalaldeen , Mohamed Razi (LAMBERT Academic Publishing, 2014)
This study investigates the knowledge management (KM) readiness of the Sri Lankan telecommunication industry and the factors that contribute to KM Readiness. As the scope of the KM is very wide, this study was confined only to the knowledge creation and sharing processes of KM. Data were collected from 313 executives of seven companies in the Sri Lankan Telecommunication Industry using self-administered questionnaires. This study considered KM enablers, such as organisational culture, structure, and IT infrastructure, and individual acceptance factors, such as performance expectancy and effort expectancy of KM, as the contributing factors to the KM readiness. The study found that the executives in the Sri Lankan telecommunication industry are ready for knowledge creation and sharing. In addition, all KM enablers and factors of individual acceptance except informal organisational structure were significantly and positively correlated with KM readiness. There were five significant predictors of KM readiness; three KM enablers and two individual acceptance factors; namely ‘trust & collaboration’, ‘IT support’, ‘ICT use & support for search and sharing’, ‘performance expectancy of KM’, and ‘effort expectancy of KM’. Furthermore, the study found that gender moderates the relationship between ‘IT support’, ‘ICT use & support for search and sharing’, ‘performance expectancy of KM’ and KM readiness. Age moderates the relationship between ‘IT support’ and KM readiness. In terms of theoretical contribution, the study integrates both KM and information systems (IS) perspectives to develop a theoretical model that explores the concept of KM readiness. From the practical contribution perspective, managers in the knowledge intensive organisations in Sri Lanka could use the measures to evaluate the KM readiness of their respective organisations before embarking on the implementation of KM processes.